2021
DOI: 10.1111/efp.12720
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Verticillium nonalfalfae via root contact from inoculated Ailanthus altissima in close‐to‐nature conditions

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…As a biological control of invasive species, Shahrtash and Brown (2021) suggested that a microbiological approach could be promising, but this view should be further studied. This method was successful for individuals of A. altissima from the experiment of Dubach et al (2021) who did not survive the infestations with fungus Verticillium nonalfalfae, but this also affected an individual of Quercus petraea, suggesting that it could not be a completely safe method for the local flora. Another identified biological control measure was sheep grazing, which also has disadvantages on the health of the sheep and the quality of the products supplied from them (Zihare et al, 2019).…”
Section: Methods Of Invasive Plant Control -Classical and Modern Appr...mentioning
confidence: 99%
“…As a biological control of invasive species, Shahrtash and Brown (2021) suggested that a microbiological approach could be promising, but this view should be further studied. This method was successful for individuals of A. altissima from the experiment of Dubach et al (2021) who did not survive the infestations with fungus Verticillium nonalfalfae, but this also affected an individual of Quercus petraea, suggesting that it could not be a completely safe method for the local flora. Another identified biological control measure was sheep grazing, which also has disadvantages on the health of the sheep and the quality of the products supplied from them (Zihare et al, 2019).…”
Section: Methods Of Invasive Plant Control -Classical and Modern Appr...mentioning
confidence: 99%